2010
DOI: 10.1097/ccm.0b013e3181f17c0e
|View full text |Cite
|
Sign up to set email alerts
|

Functional recovery in acute traumatic spinal cord injury after transplantation of human umbilical cord mesenchymal stem cells

Abstract: Treatment with human umbilical cord mesenchymal stem cells can facilitate functional recovery after traumatic spinal cord injury and may prove to be a useful therapeutic strategy to repair the injured spinal cord.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(65 citation statements)
references
References 53 publications
4
59
1
Order By: Relevance
“…Of note, these neuroprotective effects were associated with immunomodulation (a decrease in the microglial and astrocytic responses) and with increased Review Dalous et al levels of human growth factors such as basic fibroblast growth factor and NT-3. Hu et al obtained similar results, and showed, using an antibody against human nuclei to identify transplanted cells, that large numbers of cells survived for at least 8 wk but remained undifferentiated in the host spinal cord (96). They also observed higher expression levels of glial-derived neurotrophic factor and NT-3 in animals that had received hUCMSCs 3 wk earlier.…”
Section: Effect Of Huc-mscs In Adult Preclinical Models Of Neurologicsupporting
confidence: 62%
“…Of note, these neuroprotective effects were associated with immunomodulation (a decrease in the microglial and astrocytic responses) and with increased Review Dalous et al levels of human growth factors such as basic fibroblast growth factor and NT-3. Hu et al obtained similar results, and showed, using an antibody against human nuclei to identify transplanted cells, that large numbers of cells survived for at least 8 wk but remained undifferentiated in the host spinal cord (96). They also observed higher expression levels of glial-derived neurotrophic factor and NT-3 in animals that had received hUCMSCs 3 wk earlier.…”
Section: Effect Of Huc-mscs In Adult Preclinical Models Of Neurologicsupporting
confidence: 62%
“…12 Finally, once isolated from host tissue, MSCs can be expanded rapidly ex vivo, which enables prompt clinical administration. 13 In view of these advantages, MSCs have become an active focus of investigation for a wide range of diseases, such as ischaemic cardiomyopathy, 14 chronic obstructive pulmonary disease, 15 acute neurological injuries, 16 graft-versus-host disease, 17 sepsis, and acute lung injury.…”
Section: Mscs Overviewmentioning
confidence: 99%
“…Significant subsets of grafted cells expressed the neuron-specific beta-III tubulin, the GABAergic marker glutamate decarboxylase 67 (GAD67), the oligodendrocyte markers RIP or myelin basic protein (MBP) (Sieber-Blum et al, 2006). More interestingly, functional improvement was shown by two independent approaches, spinal somatosensory evoked potentials (SpSEP) and the SemmesWeinstein touch test (Hu et al, 2010). The strength of NSCS was fully characterized as they can exert a combination of pertinent functions in the contused spinal cord, including cell replacement, neuroprotection, angiogenesis and modulation of scar formation.…”
Section: Spinal Strokementioning
confidence: 99%